Pengaruh Budaya Organisasi Dan Employee Engagement Terhadap Kinerja Karyawan di PT. PLN (Persero) Up3 Flores Bagian Timur Maumere Kabupaten Sikka - Maria Yustanti Deta; Antonius Philippus Kurniawan; Margaretha Yulianti (Universitas Nusa Nipa Maumere, 2023)
.The Influence of aimed to (1) determine the descripition of performance, organization culture, and employee engagement; (2) analyse the influence of organization culture and employee engagement on employee performance both partially and simultaneously.The population in this study were 50 employees of PT PLN (Persero) UP3 East Flores. Due to the limited population, this research was conducted through census or saturated sampling. Data were collected through questionnaires and analysed using descriptive and inferential statistical methods, which was multiple linear regression. Hypothesis testing was carried out through the F test t test.The results of descriptive analysis showed that the variabels of employee performance, organizational culture and employee engagement were categorized as good. The statistical results of the t test indicated that partially ,organizational culture variabels have a significant effect on employee performance, while simultaneously employee engagement has an insiginificant effect on employee performent variabels. The results of the F test statistics indicated that simultanesously the variabels of organizational culture and employee engagement have a significant effect on employee performance.The results of the determination alalysis showed that the two independent variabels in this study were able to explain the variation in the fluctuation of employee performance of PT PLN (Peresro) UP3 Eastern Flores Maumare Sikka Regency by 75%